Analisis Jenis dan Kelimpahan Mikroplastik di Perairan Pantai Seraya, Kota Balikpapan - Maulia, Risnanda; Eryati, Ristiana; Ritonga, Irwan Ramadhan (Universitas Bangka Belitung, 2026)
Microplastics in waters is one of the problems in the coastal and marine environment. One of the areas affected by microplastics in coastal areas is the tourism beach. The purpose of this study was to determine the type and abundance of microplastics in the waters. This research was conducted in April - January 2023 at Seraya Beach, Balikpapan City. The data collection method was descriptive quantitative by describing and calculating the total abundance of microplastics. Water sampling was conducted at the sea surface (0-50 cm) during low tide condition. The research data were analysed by counting the total number of microplastic particles found, grouped, and calculated the abundance of microplastics using Microsoft Ofiice Excel and SPSS software. It was found that the type of microplastics in Seraya Beach was fragments (4666 particles), followed by fibres (560 particles) and films (218 particles). The fragment type was the dominant microplastic type in Seraya Beach waters with a total of 4666 particles, followed by fibre (560 particles) and film (218 particles). A significant difference (p<0.05) was found between the abundance and type of microplastics in Seraya Beach waters. In general, the presence of microplastics in Seraya Beach is influenced by geographical location, tourist activities on the beach and historical factors.